PENGARUH UKURAN PERUSAHAAN, FINANCIAL DISTRESS, AUDITOR SWITCHING DAN PANDEMI COVID-19 TERHADAP AUDIT DELAY - Hani Frimmantuti; Wisnu Julianto (Politeknik Raflesia Press, 2022)
This study is a quantitative study that aims to examine the effect of firm size, financial distress, auditor switching and the COVID-19 pandemic on audit delay. This study uses data from the financial statements of food and beverages companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sample of this study amounted to 22 food and beverages companies listed on the Indonesia Stock Exchange during 2018-2020. The analytical technique used is multiple linear regression analysis using the SPSS version 24 application program. The results of this study indicate that 1) company size has a negative and significant effect on audit delay; 2) financial distress has no effect on audit delay; 3) auditor switching has no effect on audit delay; 4) the COVID-19 pandemic has no effect on audit delay and there is no difference in audit delay before the COVID-19 pandemic and after the COVID-19 pandemic.